State and Federal Institutions in Amapa/ Brazil: Age-Grade Distortion Rate in High School (2016-2018) (Research, Society and Development, 2020)
The Federal Institutes of Science and Technology Education are responsible for offering technical vocational secondary education, in the form of integrated courses, for those who finish elementary school and for the public of youth and adult education. The cycle of compulsory and free basic education must be from four to seventeen years old and the student who is not at the correct age during this cycle, is included in a situation of age-grade distortion. The purpose of this article is to show the age-grade distortion rate in State and Federal high school entities in Amapá between 2016 and 2018. The survey was conducted in the INEP database (http.//inep.gov.br). What the data reveals about the phenomenon of age-grade distortion in high school, in the state of Amapá, mainly in the state public school system, is very worrying. It is necessary to create conditions so that students can do their studies at the correct age, as the gap generates a strong impact on school life causing problems such as demotivation, failure and even dropping out of school.